An Islamic Business Ethics Review of Price Setting Practices in Catering Enterprises - Abidin; Marwendi, Reza Okva (Zabags International Journal of Engagement, 2025)
Price-setting in micro-enterprises, especially in the catering sector, is a critical element that reflects the ethical integrity of business transactions. In Muslim-majority regions such as Talang Babat, pricing ideally adheres to Islamic business ethics, which emphasize justice, transparency, and the avoidance of exploitative practices. This study aims to describe and analyze the pricing practices employed by catering business actors in Talang Babat through the lens of Islamic business ethics. Using a qualitative phenomenological approach, data were collected through interviews, observations, and documentation involving catering entrepreneurs, customers, and religious or community leaders. The findings show that while Islamic values are generally acknowledged, the practical implementation of ethical principles in pricing remains partial and inconsistent—particularly concerning transparency, fairness, and cost justification. This article contributes to the limited empirical literature on sharia-based pricing among micro-service enterprises and offers recommendations to strengthen the ethical foundations of small business practices in Muslim-majority settings.